Blood glucose and insulin and correlation of SLC25A13 mutations with biochemical changes in NICCD patients. Issue 12 (June 2017) - Lu, Chun-Ting; Shi, Qi-Ping; Li, Ze-Jian; Li, Jiong; Feng, Lie
Neonatal intrahepatic cholestasis caused by citrin deficiency (NICCD) is a hereditary metabolic disease arising from biallelic mutations of SLC25A13 . This study aimed to explore the characteristics of fasting blood glucose (FBG), fasting insulin (FINS) and C-peptide (C-P) levels in NICCD infants, analyze their SLC25A13 genetic mutations and further discuss the correlation between SLC25A13 genetic mutations and biochemical changes. Seventy-two cases of infants with cholestasis disease were gathered. Among them, 36 cases with NICCD diagnosis were case group. Meanwhile, 36 cases with unknown etiology but excluded NICCD were control group. FBG, FINS, C-P, ALT, AST, GGT, ALP, TG, HDL-C, LDL-C and Non-HDL-C were collected from all subjects, and DNA was extracted from venous blood for SLC25A13 mutations detection. The incidence of hypoglycemia was 3% in NICCD group. There were no significant statistical difference of FBG, FINS and C-P between NICCD and INC groups ( P >  0.05). ALT, LDL-C and Non-HDL-C levels in NICCD group were lower than the INC group, while SLC25A13 mutations were associated with the level of GGT ( P <  0.05). Ten different SLC25A13 genetic mutations were detected, among which, 851del4, IVS16ins3kb, IVS6+5 G > A and 1638ins23 mutations made up 82% of all mutations. The incidence of hypoglycemia may be higher in small gestational age infants with NICCD. Low LDL-C may be one of the characteristics of dyslipidemia in NICCD infants. There was a correlation between SLC25A13 gene mutations distribution and the GGT level, but the meaning of this finding remains to be further in-depth study. Impact statement: This study aims to compare FBG, FINS, C-P, other biochemical and clinical manifestations between NICCD and non-NICCD infants, and discuss differential diagnosis of NICCD and INC beyond the genetic analysis. And investigate the correlation between SLC25A13 genetic mutations and biochemical changes. This work presented that incidence of hypoglycemia may be higher in small gestational age infants with NICCD. Low LDL-C may be one of the characteristics of dyslipidemia in NICCD infants. There was a correlation between SLC25A13 gene mutations distribution and the GGT level.